Desain Agroforestri Pada Lahan Gambut Di Kota Palangka Raya Kalimantan Tengah: Agroforestry Design on Peat Land in Palangka Raya City, Central Kalimantan - Josua Parlaungan Ujung; Afentina; Yanarita (JURNAL HUTAN TROPIKA, 2026)
Peatlands in Palangka Raya City have the potential to be developed through sustainable agroforestry systems, but their utilization still faces various biophysical constraints such as high acidity, variations in peat depth and maturity, and fluctuations in groundwater levels. This study aims to (1) identify the biophysical characteristics of peatlands, (2) identify plant species suitable for agroforestry on peatlands, and (3) design an agroforestry design that is appropriate to site conditions and supports the ecological sustainability of the community. Research methods included field observations, measurements of peat depth and maturity, measurements of groundwater levels, and analysis of plant suitability. Data were analyzed descriptively to determine plant patterns and combinations that are adaptive to peat conditions. The results indicate that the peatlands at the study site are acidic with relatively shallow groundwater levels, and the peat maturity conditions influence plant species selection. The recommended agroforestry design combines forestry and agricultural/plantation crops in a mixed pattern tailored to the biophysical characteristics of the land. This system has the potential to increase land productivity, maintain water stability, and reduce the risk of degradation and fire. Thus, agroforestry can be an alternative for productive, environmentally friendly, and sustainable peatland management in Palangka Raya City.